2008
DOI: 10.1002/ajhb.20768
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational gains in relative knee height as compared to gains in relative leg length within Taiwanese families

Abstract: Evidence indicates that variation in relative leg length (RLL) is a sensitive indicator of early childhood circumstances, but research presents conflicting evidence of how lower leg growth contributes to variability. This study investigates the extent of intergenerational changes in subischial leg length and knee height relative to stature among father-son, mother-daughter, and midparent-offspring pairs. These changes and differences in the extent of mean change in the two indices within like-sex parent-offspr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Fifty six of these families were represented by a son while 51 families were represented by a daughter. Details of recruitment and measurement procedures for the first group of families contacted in 2003 are reported elsewhere (Floyd, ). The same procedures were used to gather information from 27 additional Taiwanese families in 2007.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Fifty six of these families were represented by a son while 51 families were represented by a daughter. Details of recruitment and measurement procedures for the first group of families contacted in 2003 are reported elsewhere (Floyd, ). The same procedures were used to gather information from 27 additional Taiwanese families in 2007.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…We hypothesized that there might be an intrauterine effect of maternal height on child stunting, and a child born to the shortest mother and father might have the highest risk of being stunted. In addition, some existing studies found that there was a sex-specific or age-specific parental-offspring association (18)(19)(20), whereas some others did not (21). Therefore, we also attempted to explore such associations based on much larger sample size.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, leg length (LL) is more sensitive to early life nutrition than are other components of stature growth, making it a useful retrospective index of early life nutrition (Bogin et al, 2002;Gunnell, 2002;Krogman, 1972;Leitch, 1951;Li et al, 2007;Scammon, 1930;Scrimshaw and B'Ehar, 1965;Tanner, 1978;Wadsworth, 2002). Evidence for this comes from studies that directly measure early nutrition in low-income populations (Bogin et al, 2002;Frisancho et al, 2001), while improvements in socioeconomic conditions have also been shown to primarily reflect increases in leg growth (Bogin and Keep, 1999;Floyd, 2008;Sanna and Soro, 2000).…”
mentioning
confidence: 99%